Generation and Characterization of Functional Human Hypothalamic Neurons. Issue 1 (13th February 2018) - Kirwan, Peter; Jura, Magdalena; Merkle, Florian T.
Abstract: Neurons in the hypothalamus orchestrate homeostatic physiological processes and behaviors essential for life. Defects in the function of hypothalamic neurons cause a spectrum of human diseases, including obesity, infertility, growth defects, sleep disorders, social disorders, and stress disorders. These diseases have been studied in animal models such as mice, but the rarity and relative inaccessibility of mouse hypothalamic neurons and species‐specific differences between mice and humans highlight the need for human cellular models of hypothalamic diseases. We and others have developed methods to differentiate human pluripotent stem cells (hPSCs) into hypothalamic neurons and related cell types, such as astrocytes. This protocol builds on published studies by providing detailed step‐by‐step instructions for neuronal differentiation, quality control, long‐term neuronal maintenance, and the functional interrogation of hypothalamic cells by calcium imaging. Together, these protocols should enable any group with appropriate facilities to generate and study human hypothalamic cells. © 2017 by John Wiley & Sons, Inc.